2022
DOI: 10.3390/en15217908
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water and Cyclic Loading on Ultrasonic and Mechanical Properties of Sandstone: An Experimental Study

Abstract: In this study, the water absorption, mechanical properties, and energy evolution characteristics of sandstone were examined through experimental and theoretical analysis. The P-wave velocity was found to initially decrease, then increased with immersion time and water content. The water absorption rates of three sandstone specimens decreased with immersion time and water content. The post-peak deformation of the sandstone changed from brittle failure to strain softening. With the increase in water content, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Rao et al 50 found a decrease from 2.21 to 1.17 in the temperature range of 250–300 °C. Whereas, Chen et al 51 observed the tensile strength reduction from 1.17 to 0.91 in the temperature range of 200–800 °C. Similarly, Yang et al 39 found a reduction of tensile strength from 1.28 to 0.43 within the temperature range of 500–900 °C.…”
Section: Resultsmentioning
confidence: 92%
“…Rao et al 50 found a decrease from 2.21 to 1.17 in the temperature range of 250–300 °C. Whereas, Chen et al 51 observed the tensile strength reduction from 1.17 to 0.91 in the temperature range of 200–800 °C. Similarly, Yang et al 39 found a reduction of tensile strength from 1.28 to 0.43 within the temperature range of 500–900 °C.…”
Section: Resultsmentioning
confidence: 92%
“…If the temperature exceeded 800 degrees, sandstone would completely change from shear failure or tensile failure to total collapse. But before 800 degrees, the shear strength of sandstone only fluctuated slightly [32]. The peak shear strength, residual shear strength and terminal normal stress all display an exponential variation with temperature, i.e., initial fluctuations or a slight increase, then a dramatic decrease, achieving a threshold temperature of 400 • C. The secant peak shear stiffness declines by 43.79-70.48% in a temperature range of 400-800 • C due to enhanced ductility and decreasing peak shear strength [33].…”
Section: Macroscopic Mechanical Propertiesmentioning
confidence: 97%